Mathematical and computer models for predicting greenhouse gas emissions from soil into the atmosphere: review and comparison - Shostak, Liubov; Stepanchenko, Olha; Martyniuk, Petro; Belozerova, Olena (Моделювання, керування та інформаційні технології, 2023)
Climate change is one of the pressing global issues facing humanity. Greenhouse gases play a pivotal role in this process, as they are emitted from the soil and interact with the atmosphere, altering the climate balance. This article explores mathematical and computer models used to estimate the volumes of gas emissions from the soil, aiming to identify current and effective approaches for monitoring such emissions, taking into account land use types. Essential parameters for modeling greenhouse gas migration processes and monitoring their impact on climate change are defined. In this study, we undertake a comparative analysis of models used to assess this process, considering climatic conditions, soil type, and particle size distribution, is provided. The results of model comparisons can be employed to evaluate greenhouse gas emissions, study their influence on climate change, and develop strategies to combat global warming. Keywords—greenhouse gases, carbon dioxide, soil respiration, mathematical model, information system, carbon, methane, soil organic matter